YIIFSWA II OPENDAY - Interview with John Ikeorgu - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Interview with Dr. John Ikeorgu, NRCRI, Nigeria at YIIFSWA II OPENDAY at IITA Ibadan. YIIFSWA-II showcases High Ratio Propagation Technologies and demonstrates large scale production of early generation seed yam.